New records of Myotis alcathoe in Ukraine - Bashta, A.-T.; Ivashkiv, I.; Krokhmal, A. (Theriologia Ukrainica, 2018)
A male Myotis alcathoe (FA = 32,1 mm, D5 = 41 mm, G = 4,1 g) was caught using mist-net on 12 September 2016 near the entrence of the Medova Cave (49°49'16,3"N, 24°05'23"E; 357 m a.s.l.), which is located in the southeastern outskirts of Lviv city (Western Ukraine). This is the first record of M.alcathoe in the city of Lviv. Observations of M. alcathoe at the cave entrance during the swarming period confirms the use of underground shelters by this species for hibernation. The species is part of the bat communities of old deciduous forests, which was confirmed by ultrasound investigations in summer. Самець Myotis alcathoe (FA = 32,1 мм, D5 = 41 мм, G = 4,1 г) був зловлений за допомогою павутинної сітки 12.09.2016 р. на вході до Медової печери (49°49’16,3”N, 24°05’23”E; 357 м над р. м.), яка розташована на південно-східній околиці м. Львів (Західна Україна). Ця знахідка є першим підтвердженням наявності цього виду на території м. Львова. Спостереження особини M. alcathoe біля входу в печеру під час періоду «роїння» підтверджує можливість використання підземних схованок для гібернації. У прилеглих лісах M. alcathoe є частиною угруповання кажанів старих широколистяних лісів, що підтверджене ультразвуковими дослідженнями у літній період.